2020
DOI: 10.3390/ijms22010049
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor in Energy Balance: The Road from Dioxin-Induced Wasting Syndrome to Combating Obesity with Ahr Ligands

Abstract: The aryl hydrocarbon receptor (AHR) has been studied for over 40 years, yet our understanding of this ligand-activated transcription factor remains incomplete. Each year, novel findings continually force us to rethink the role of the AHR in mammalian biology. The AHR has historically been studied within the context of potent activation via AHR agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), with a focus on how the AHR mediates TCDD toxicity. Research has subsequently revealed that the AHR is actively invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 122 publications
0
23
0
Order By: Relevance
“…The aromatic hydrocarbon receptor (AhR) is distributed in almost all tissues in various mammals and is expressed abundantly in the placenta, liver, and lungs, where it plays multiple roles in regulating the immune response, carcinogenesis, metabolic diseases, and neurophysiology ( Xue et al, 2018 ; Girer et al, 2020 ; Vogel et al, 2020 ). In the gut, AhR is expressed in epithelial cells and immune cells ( Nguyen et al, 2013 ; Ikuta et al, 2016 ).…”
Section: The Effects Of Indole and Its Derivativesmentioning
confidence: 99%
“…The aromatic hydrocarbon receptor (AhR) is distributed in almost all tissues in various mammals and is expressed abundantly in the placenta, liver, and lungs, where it plays multiple roles in regulating the immune response, carcinogenesis, metabolic diseases, and neurophysiology ( Xue et al, 2018 ; Girer et al, 2020 ; Vogel et al, 2020 ). In the gut, AhR is expressed in epithelial cells and immune cells ( Nguyen et al, 2013 ; Ikuta et al, 2016 ).…”
Section: The Effects Of Indole and Its Derivativesmentioning
confidence: 99%
“…The AhR is a highly conserved transcription factor that integrates environmental cues and metabolic processes, particularly the regulation of energy metabolism. 63,64 Mice expressing a constitutively active form of AhR spontaneously develop hepatic steatosis, possibly secondary to increased fatty acid import, suppression of fatty acid oxidation, and increased oxidative stress. 65 Global Ahr loss enhances insulin sensitivity and glucose tolerance and reduces the activity of the PPARα pathway that regulates fatty acid oxidation and glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-mir-199a-5p [698], GATA2 [706], FOXP2 [707] and AHR (aryl hydrocarbon receptor) [708] have been demonstrated to function in hypertension, but these genes might be novel targets for NAFLD. Previous studies have demonstrated that hsa-mir-22-5p [709], hsa-mir-150-5p [710], RUNX1 [711], TP53 [712], AHR (aryl hydrocarbon receptor) [713] and TRIM28 [714] are an independent prognostic factor in obesity and might be associated with obesity pathogenesis, but these genes might be novel targets for NAFLD. Wang et al [715], Lu et al [716], Shi et al [717], Yu et al [718], Zhang et al [719] and Ren et al [720] reported that altered expression of hsa-mir-3613-3p, hsa-mir-103a-3p, hsa-mir-150-5p, GATA2, RUNX1 and AHR (aryl hydrocarbon receptor) correlated in patients with kidney disease, but these genes might be novel targets for NAFLD.…”
Section: Discussionmentioning
confidence: 99%